A single-arm feasibility study of gradual dose de-escalation of antiemetic dexamethasone for older patients receiving chemotherapy. Issue 6 (July 2021) - Suh, Koung Jin; Yoon, Seonghae; Kim, Jin Won; Yoon, Seo Hyun; Kim, Ji-Won; Kim, Se Hyun; Kim, Yu Jung; Lee, Keun-Wook; Lee, Jong Seok; Kim, Jee Hyun
Abstract: Objectives: To investigate whether discontinuation of prophylactic dexamethasone by gradual dose de-escalation is practicable in older patients with cancer undergoing moderately emetogenic chemotherapy. Materials and Methods: This single-arm, feasibility study prospectively enrolled 40 patients (≥70 years old) with colorectal cancer, who were scheduled to undergo adjuvant FOLFOX chemotherapy, and ten patients ≤60 years old to serve as a control group for pharmacokinetic study. All patients received an antiemetic regimen consisting of intravenous dexamethasone 8 mg and palonosetron at day 1 of the first cycle and underwent phone interviews using symptom questionnaires at day 7 of each cycle. Dexamethasone was tapered off through gradual de-escalation by 2 mg per cycle, when complete response (CR; no emesis and no rescue therapy) was achieved. Primary endpoint was the proportion of patients who discontinued dexamethasone completely. Results: The median age of the patient was 74 years, and 50% were male. Of the 40 patients, 36 completed twelve cycles of chemotherapy, and 73% ( N = 29) were able to discontinue dexamethasone completely. The mean (±SD) dose of dexamethasone per cycle was 3.0 mg (±2.4 mg), which was reduced to 37.5% of the initial dose level. The severity of patient-reported nausea did not significantly change over chemotherapy cycle. Geriatric assessment revealed no decline in any domain and fasting blood glucose and hemoglobin A1c levels were not elevated after twelve cycles of chemotherapy, compared to the baseline. Conclusion: Gradual dose de-escalation and discontinuation of prophylactic dexamethasone is feasible without compromising its antiemetic effect in older patients undergoing chemotherapy.